Go clean label: replacement of commercial dough strengtheners with hard red spring wheat flour in bread formulations - Rahman, Md Mahfuzur (J Food Sci Technol, 2020)
There is growing interest in the application of natural ingredients to replace chemical dough improvers in bread formulations in order to meet consumer demands of clean label products. The goal of this study was to evaluate the dough quality and baking quality of hard red spring (HRS) wheat flour blends to replace commercial dough improvers. Hard red winter (HRW) wheat flour is commonly used in bread and diner roll formulations. In this study, doughs were prepared by adding 10%, 20%, 30%, and 40% of HRS wheat flour to HRW wheat base-flour to compare the dough quality and baking quality relative to different levels of commercial improvers. Additional to commercial HRS flour, two commonly grown HRS wheat varieties (Glenn and Linkert) were included in the study. All of the HRS wheat flour blends had significantly (p < 0.05) higher farinograph stability and extensograph resistance at 135 min than doughs containing most of the commercial additives. Bread flour with 40% Glenn and 40% Linkert showed the highest loaf volumes of 920 cm(3) and 950 cm(3), respectively with the firmness of 1553.50 and 1525.50 mN, respectively. Baking quality of HRS wheat flour blends also showed significant (p < 0.05) correlation with dough rheology but commercial additives did not have the correlations. Therefore, HRS wheat flour may be used as a replacement for dough improvers, as it had better dough and bread properties compared to commercial additives and provides a great alternative for “clean-label” bread products.